2017
DOI: 10.1021/acs.est.7b01727
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective River Water Quality Management using Integrated Real-Time Control Technology

Abstract: Integrated real-time control (RTC) of urban wastewater systems is increasingly presented as a promising and emerging strategy to deliver improved surface water quality by responsive operation according to real-time data collected from the sewer system, treatment plant, and the receiving water. However, the detailed benefits and costs associated with integrated RTC have yet to be comprehensively evaluated. Built on state-of-the-art modeling and analytical tools, a three-step framework is proposed to develop int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…With a better understanding of the interdependency and complexity of various processes and systems in a catchment, the utilization of water resources must be considered from an integrated perspective, including the integration of physical, chemical and ecological processes; integration of information and communications technology (ICT) and infrastructure [44]; and cooperation between institutions and stakeholders. Meanwhile, growing populations and economic activities increase the demands on food, energy and water, and their nexus needs to be addressed in the context of deep uncertainty arising from climate change [7,45].…”
Section: Discussionmentioning
confidence: 99%
“…With a better understanding of the interdependency and complexity of various processes and systems in a catchment, the utilization of water resources must be considered from an integrated perspective, including the integration of physical, chemical and ecological processes; integration of information and communications technology (ICT) and infrastructure [44]; and cooperation between institutions and stakeholders. Meanwhile, growing populations and economic activities increase the demands on food, energy and water, and their nexus needs to be addressed in the context of deep uncertainty arising from climate change [7,45].…”
Section: Discussionmentioning
confidence: 99%
“…The default parameters should thus always be evaluated for their sensitivity, e.g., by using Morris screening [52], as done here, or by applying other methods [40,54,63]. Influential parameters can be further modified by the modeler until a desirable outcome is reached, either by manually adjusting them in a trial-and-error manner, or based on expert knowledge or through the use of optimization routines [64]. The final parameterization is then to be modified by means of a long-term simulation, ideally using spatially-variable rainfall where available.…”
Section: Discussionmentioning
confidence: 99%
“…Though the procedure in its current form has been shown to be useful for cases using CSO volume and flooding as evaluated criteria (also used by the majority of RTC related literature [25]), its applicability might be limited to cases where water-quantitative evaluation criteria are used. Though water quality or impact-based control, as recently demonstrated for several case studies [64,65], might be a desirable application, this may require the implementation of a different approach for control location selection.…”
Section: Discussionmentioning
confidence: 99%
“…Kondolf et al (2014) investigated the impacts of rapid development of hydropower dams and found that an unprecedented boom of hydropower dams might result in a greater sediment starvation, leading to a profound effect on downstream productivity of the Mekong River (Winemiller, 2017). (Stillwell et al, 2010), integrated real time control (Meng et al, 2017), and operational permitting (Meng et al, 2016). In contrast, Although above one-way impact studies facilitate preliminary assessments of nexus impacts and trade-offs, they merely draw a partial picture of nexus systems and manifest limited capacity in nexus analysis owing to their inability to reflect feedback and second-round effects (Ferroukhi et al, 2015).…”
Section: One-way Impact Analysismentioning
confidence: 99%